Vaginal colonization of extended-spectrum beta-lactamase-producing bacteria during pregnancy: An observational study. (March 2020) - Foessleitner, Philipp; Gasser, Julia; Kiss, Herbert; Flunt, Albert; Presterl, Elisabeth; Petricevic, Ljubomir; Farr, Alex
Abstract: Objective: Extended-spectrum beta-lactamase (ESBL) is a rapidly evolving enzyme that cleaves beta-lactam-containing antibiotics, forming resistance to certain types of antibiotics, such as penicillin, cephalosporins and monobactams. Colonization with ESBL-producing bacteria during pregnancy is harmful, however this topic is currently underrepresented in the literature. Study design: Using a retrospective design, we analyzed data of all consecutive pregnant women who were identified with a vaginal colonization of ESBL-producing bacteria from 2011 to 2016 at the Medical University of Vienna, Department of Obstetrics and Gynecology. Swabs were taken during pregnancy and/or at delivery, as well as from neonates. Demographic and clinical data were obtained from the central in-house alert system and patients' clinical records. Results: Of the 14, 279 deliveries performed in our department during the study period, we identified 13 women with vaginal colonization of ESBL-producing bacteria during pregnancy. Of these cases, 6 born neonates were tested ESBL positive. The maternal-to-neonatal transmission rate was 43 %, associated with a 70 % rate of preterm premature rupture of the membranes (pPROM) and a preterm birth rate of 83 %. Of the 6 neonates with ESBL colonization, 4 neonates (67 %) were born to mothers who were still tested positive at the time of delivery. Conclusion: Maternal colonization of ESBL-producing bacteria is an important risk factor for transmission. The vaginal presence of ESBL-producing bacteria during pregnancy is associated with preterm birth and pPROM, which shows the need for clear diagnostic and therapeutic guidelines.